Expanded Hematopoietic Progenitor Cells Reselected for High Aldehyde Dehydrogenase Activity Demonstrate Islet Regenerative Functions. (19th January 2016) - Seneviratne, Ayesh K.; Bell, Gillian I.; Sherman, Stephen E.; Cooper, Tyler T.; Putman, David M.; Hess, David A.
Abstract: Human umbilical cord blood (UCB) hematopoietic progenitor cells (HPC) purified for high aldehyde dehydrogenase activity (ALDH hi ) stimulate islet regeneration after transplantation into mice with streptozotocin-induced β cell deletion. However, ALDH hi cells represent a rare progenitor subset and widespread use of UCB ALDH hi cells to stimulate islet regeneration will require progenitor cell expansion without loss of islet regenerative functions. Here we demonstrate that prospectively purified UCB ALDH hi cells expand efficiently under serum-free, xeno-free conditions with minimal growth factor supplementation. Consistent with the concept that ALDH-activity is decreased as progenitor cells differentiate, kinetic analyses over 9 days revealed the frequency of ALDH hi cells diminished as culture time progressed such that total ALDH hi cell number was maximal (increased 3-fold) at day 6. Subsequently, day 6 expanded cells (bulk cells) were sorted after culture to reselect differentiated progeny with low ALDH-activity (ALDH lo subset) from less differentiated progeny with high ALDH-activity (ALDH hi subset). The ALDH hi subset retained primitive cell surface marker coexpression (32.0% ± 7.0% CD34 + /CD38 − cells, 37.0% ± 6.9% CD34 + /CD133 + cells), and demonstrated increased hematopoietic colony forming cell function compared with the ALDH lo subset. Notably, bulk cells or ALDH lo cells did not possess the functional capacity to lower hyperglycemia after transplantation into streptozotocin-treated NOD/SCID mice. However, transplantation of the repurified ALDH hi subset significantly reduced hyperglycemia, improved glucose tolerance, and increased islet-associated cell proliferation and capillary formation. Thus, expansion and delivery of reselected UCB cells that retain high ALDH-activity after short-term culture represents an improved strategy for the development of cellular therapies to enhance islet regeneration in situ.